PELATIHAN PELAYANAN PRIMA KARYAWAN WARUNG MIE AYAM DAN BAKSO HOMEMADE DI PINANG RAYA - Rades Suryati Baha Sendi; Naura Marisa Hendrawan; Khairunnisa Khairunnisa; Tazkya Aulya; Muthia Oktaviani (PUAN INDONESIA, 2026)
This community service activity aims to improve service excellence among the employees of Warung Mie Ayam & Bakso Homemade on Jalan Pinang Raya, Pondok Labu, South Jakarta, enabling them to provide friendly, fast, and responsive service to customers. The activity was carried out in four stages: an initial observation and interview, development of training materials, implementation of training consisting of lectures and service simulations (role play) for employees, and an evaluation using observation checklists before and after the training. Following the training, the employees showed improvement in applying smiles, greetings, and polite salutations, in responding to orders more quickly, and in handling customer complaints compared with the pre-training condition. These findings indicate that service excellence training is effective in improving the service quality of small-scale culinary MSME employees and has the potential to increase customer satisfaction and loyalty toward the mie ayam and bakso stall.